Tax knowledge and tax avoidance: The case of mining companies listed on Indonesia - Tiong, Ka; Ismail, Tubagus; Yazid, Helmi; Taqi, Muhamad (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this research is to know and analyze the influence of tax knowledge towards tax avoidance. The sample technique used is a purposive sampling from a method of judgment non-probability sampling and the analysis technique is using the ordinary least square method. The outcome of the research shows a significant influence of tax knowledge towards tax avoidance. A result of negative beta coefficient unstandardized indicates the higher tax knowledge owned by a top manager, the lower and even zero tax avoidance behavior is likely to happen. On the contrary, if the top manager has a lower tax knowledge, then the tendency towards tax avoidance behavior is high. The tax avoidance practice is chosen in order to achieve more profit for the company.